Монгол Улсын олон тулгуурт гадаад бодлого Хятадын аюулгүй байдалд нөлөөлөх нь (Journal of International Studies, 2005)
English title: Multipolar foreign policy of Mongolia and its influence on the security of Chinatranslated by B.Indra